(untitled) (Progressive Agriculture, 2017)
Ten rice genotypes were evaluated for association studies of yield and its contributing traits to select the traits for yield improvement in submerged condition. An experiment was conducted in the experimental field of Bangladesh Institute of Nuclear Agriculture (BINA) and 15 morphological traits Viz. Days to flowering (days), plant height (cm), Tiller number plant-1 , (Nos.), effective tiller number plant-1 (Nos.), 100 seed weight (g), harvest index (%) etc. were studies to measure nature of association between these traits and yield. Correlation studies showed total tiller number plant-1 (0.661), effective tiller number plant-1 (0.694), flag leaf breadth (0.651), fresh weight (0.705), dry weight (0.700) and harvest index (0.689) had significantly positive relationship on yield. Path co-efficient studies indicated direct positive association of tiller number plant-1 (2.481), panicle length (2.431), Unfilled grain panicle-1 (0.033), fresh weight (0.0451), dry weight (0.166), harvest index (1.255) and chlorophyll content (1.72) with yield. Breeding for submergence tolerance of rice genotypes considering these characters could be useful for improvement yield in future. Progressive Agriculture 28 (1): 7-11, 2017